Serum biomarkers for acute hepatotoxicity of Echis pyramidum snake venom in rats - Asmari, Abdulrahman K Al (Int J Clin Exp Med, 2015)
Echis pyramidum is a venomous viper responsible for most cases of envenomation in Arabian Peninsula. We determined the acute phase (3-6 h) changes in serum markers of liver function including alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma glutamyl transferase (GGT) and bilirubin in adult male Sprague Dawley rats injected with Echis pyramidum venom (EPV) in the doses of 0.00 (control), 0.25, 0.50 and 1.00 mg/kg bodyweight. We also analyzed markers of oxidative stress including superoxide dismutase (SOD), catalase (CAT), total thiols (T-SH) and thiobarbituric acids reactive substances (TBARS) in liver. The results showed significant and dose- and time-dependent increases in serum ALT, ALP and GGT activities after a single injection of EPV. Serum bilirubin was significantly increased by medium and high doses of EVP after 3 h post-injection and then decreased at 6 h. The low dose of EPV neither affected the activity of SOD nor altered the levels of liver T-SH and TBARS, however, it significantly decreased the activity of CAT at 6 h post-injection of EPV. The medium dose of EPV significantly reduced liver SOD activity after 6 h whereas the high dose significantly reduced the SOD activity at 3 h and 6 h post-dosing. Both medium and high doses of EPV caused significant as well as dose- and time-dependent reductions in liver CAT activities. The high dose significantly reduced T-SH and increased TBARS in rat liver. Further studies are warranted to test the pharmacological potential of early phase antioxidant therapy for neutralizing the toxic effects of EPV.